Finalitas Kekristenan dan Argumentasinya yang Final - Stevri Indra Lumintang (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2019)
Abstract: No religion could ever deny the fact that there is an element of religious plurality and its influences in a plural society. Each religion possesses a claim on the finality or uniqueness of the Lord they worship and believe in. Among the Christians living in a Christian majority society, the topic of